Diabetes and Technology for Increased Activity Study: The Effects of Exercise and Technology on Heart Rate Variability and Metabolic Syndrome Risk Factors - Stuckey, Melanie I.; Kiviniemi, Antti M.; Petrella, Robert J. (Frontiers in Endocrinology, 2013)
This study tested the hypothesis that an eight-week exercise intervention supported by mobile health (mHealth) technology would improve metabolic syndrome (MetS) risk factors and heart rate variability (HRV) in a population with MetS risk factors. Participants (n=12; 3 male; aged 56.9±7.0y) reported to the laboratory for assessment of MetS risk factors and fitness (VO2max) at baseline (V0) and after eight-weeks (V2) of intervention. Participants received an individualized exercise prescription and a mHealth technology kit for remote monitoring of blood pressure (BP), blood glucose, physical activity and body weight via smartphone. Participants underwent 24-h ambulatory monitoring of R-R intervals following V0 and V2. Low and high frequency powers of HRV were assessed from the recording and the ratio of low-to-high frequency powers and low and high frequency power in normalized units were calculated. One-way repeated measures analysis of variance showed that waist circumference (V0: 113.1±11.0cm, V2: 108.1±14.7cm; p=0.004) and diastolic BP (V0: 81±6mmHg, V2: 76±11mmHg; p=0.04) were reduced and VO2max increased (V0: 31.3ml/kg/min, V2: 34.8ml/kg/min; p=0.02) with no changes in other MetS risk factors. Low and high frequency powers in normalized units were reduced (V0: 75.5±12.0, V2: 72.0±12.1; p=0.03) and increased (V0: 24.5±12.0, V2: 28.0±12.1; p=0.03), respectively, with no other changes in HRV. Over the intervention period, changes in systolic BP were correlated negatively with the changes in R-R interval (r=-0.600; p=0.04) and positively with the changes in heart rate (r=0.611; p=0.03), with no other associations between MetS risk factors and HRV parameters. Thus, this eight-week mHealth supported exercise intervention improved MetS risk factors and HRV parameters, but only changes in systolic BP were associated with improved autonomic function.